From the Clinical to the Bench: Exploring the Insulin Modulation Effects of Tacrolimus and Belatacept - Quentin Perrier; Cécile Cottet-Rouselle; Marine de-Beaumont; Johan Noble; Sandrine Lablanche (Cell Transplantation)
Calcineurin inhibitors (CNIs) are critical in preventing rejection posttransplantation but pose an increased risk of post-transplant diabetes (PTD). Recent studies show that late conversion from CNIs to belatacept, a costimulation blocker, improves HbA1c in kidney transplant recipients with PTD or de novo diabetes. This study investigates whether the observed effects on PTD stem solely from CNI withdrawal or if belatacept influences PTD independently. The study assessed the impact of tacrolimus and belatacept on insulin secretion in MIN6 cells (a beta cell line) and rat islets. Tacrolimus and belatacept were administered to the cells and islets, followed by assessments of cell viability and insulin secretion. Tacrolimus impaired insulin secretion without affecting cell viability, while belatacept showed no detrimental effects on either parameter. These findings support clinical observations of improved HbA1c upon switching from tacrolimus to belatacept. Belatacept holds promise in islet or pancreas transplantation, particularly in patients with unstable diabetes. Successful cases of islet transplantation treated with belatacept without severe hypoglycemia highlight its potential in managing PTD. Further research is needed to fully understand the metabolic changes accompanying the transition from CNIs to belatacept. Preserving insulin secretion emerges as a promising avenue for investigation in this context.